On the outcomes of teacher wellbeing: a systematic review of research - Dreer, Benjamin (Frontiers in Psychology, 2023)
Teacher well-being is a growing area of research that has seen a steady increase in publications in recent years. The subsequent need to synthesize and structure this existing research has been articulated and addressed by a handful of systematic research reviews. However, no previous reviews have examined the potential outcomes of teacher well-being as a primary theme. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, this review has identified and evaluated the studies investigating the possible outcomes of teacher wellbeing. A keyword search identified 397 records. After the records were screened, 44 research studies analyzing data from over 76,990 teachers were included in this in-depth analysis; the concepts, methods and findings of these studies were examined. The results of this review highlight the significant relationship of teacher well-being with several factors and desirable outcomes, including teachers' sleep quality, teacher retention, teacher-student relationships, and student outcomes. However, only a few of the included studies employed methodologies that support causal interpretations of these effects. In light of the present findings, this paper offers three main recommendations to support future progress in this field.